Licensing of Commensal Rodent Trappers - Frederick M. Fishel (EDIS)
The Florida Department of Agriculture and Consumer Services’ Bureau of Licensing and Enforcement (FDACS BLE) administers Limited Certification Categories to certify Governmental or Private applicators. Limited certification programs available are for Commercial Landscape Maintenance, Lawn and Ornamental, Structural, and Urban Commercial Fertilizer applicators, and Limited Commercial Wildlife Management trappers. This document will discuss the Limited Commercial Wildlife Management Trapper Certificate.